Applied homogeneous catalysis with organometallic compounds : a comprehensive handbook in four volumes - Cornils, Boy; Herrmann, W. A.; Beller, Matthias; Paciello, Rocco (Wiley-VCH Verlag GmbH & Co. KGaA, 2017)
The completely revised third edition of this four-volume classic is fully updated and now includes such topics as as CH-activation and multicomponent reactions. It describes the most important reaction types, new methods and recent developments in catalysis. The internationally renowned editors and a plethora of international authors (including Nobel laureate R. Noyori) guarantee high quality content throughout the book. A "must read" for everyone in academia and industry working in this field.- Resumé vydavatel
Keywords: katalýza; organokovové sloučeniny; catalysis; organometallic compounds; elektronické knihy; příručky; sborníky; electronic books; handbooks and manuals; papers of several authors